Architectural shop drawing of BK-1 (2F) with the reply of BRACU Resident Engineer (RFA-443_Rev A) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.